Neutrino-related questions in nuclear and astro-particle physics - Civitarese, Osvaldo (Frontiers in Physics, 2014)
Since the prediction about its existence, by Pauli, the neutrino has been, and still is, the principal object in the cross field of nuclear, particle and astroparticle physics. Issues like its mass, oscillation parameters, the mixing with sterile species and its inclusion in cold dark matter scenarios, have raised the expectations of generations of physicists, astrophysicists and cosmologists. Without doubt, the coming years may bring a major breakthrough in neutrino physics. This is a welcome note for those which are willing to cope with the challenging and intriguing aspects of this elusive particle.